The Intergluteal Fat Stripe in Patients With Hip Abductor Tears. Issue 2 (7th February 2022) - Beicker, Clint R.; Hudspeth, L. Jared; Shanley, Ellen; Tokish, John M.; Folk, Jason
Background: With a hip abductor tendon tear, widening of the intergluteal space, or "fat stripe, " is a characteristic change seen in and around the gluteus medius and minimus. Purpose: To determine the relationship of the intergluteal fat stripe in hips with pathologic abductor tears compared with the contralateral side and to evaluate the association of fat stripe size with hip-specific patient-reported outcome measures. Study Design: Case series; Level of evidence, 4. Methods: Of the 43 patients (42 female, 1 male; mean age, 56.6 years; range, 38-85 years) who underwent endoscopic gluteus medius repair, 19 met inclusion criteria of preoperative bilateral hip magnetic resonance imaging (MRI) scans and 2-year follow up. A single board-certified fellowship-trained orthopaedic surgeon (J.F.), who was blinded to outcomes, evaluated the MRI scans to measure the intergluteal fat stripe on the operative and nonoperative sides. The 2-year postoperative International Hip Outcome Tool (iHOT-12) and modified Harris Hip Score (mHHS) values were analyzed to determine their relationship to the size of the fat stripe. Statistical analysis was performed using a paired t test, and associations were determined using Pearson product correlation as well as nonparametric measurements. Results: The size of the intergluteal fat stripe differed significantly between the operative and nonoperative sides. The area of the fat stripe on the operative side was 645.73 ± 513.09 mm 2, and on the nonoperative side it was 313.47 ± 360.71 mm 2, an average of 332.36 mm 2 greater than the nonoperative side ( P = .02). The width of the fat stripe was 9.10 ± 4.60 mm on the operative side and 5.15 ± 3.87 mm on the nonoperative side, 3.95 mm greater than the nonoperative side ( P < .01). There was no correlation between the width or area of the fat stripe on the operative side and iHOT-12 or mHHS values at 2-year follow-up. Conclusion: The study findings indicated that the intergluteal fat stripe is significantly wider and has a significantly larger area in hips with abductor tears compared with unaffected hips. This did not correlate with 2-year patient-reported outcomes.